PERSONAL FINANCIAL PLANNING AND BUSINESS FINANCE IN UMKM IN ARA VILLAGE, BULUKUMBA REGENCY - S Widad Ahmad; Miftha Farild; Wahyudi Wahyudi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In an increasingly competitive economy, efficient financial management is the key to success for both individuals and businesses. Good financial planning is not only important for individuals in managing personal finances but also crucial for business continuity, especially for Micro, Small and Medium Enterprises (MSMEs). In 2023, it is estimated that the Indonesian economy will strengthen thanks to the significant contribution of MSME growth, MSMEs play a vital role as the main driver of the Indonesian economy, considering that 99% of businesses in this country are MSMEs. PKM uni aims to increase knowledge about personal finance and business finance. The method used in producing the focus of PKM objectives is Service Learning (SL), where through this approach business groups are invited to not only understand the theory of using science and technology in their business activities theoretically, but also to apply this knowledge practically. The results obtained are Based on the survey conducted, there was a positive response from the participants in the community service activities which was seen from the average of the three aspects in the survey results which were classified as very high above four. There were no significant obstacles during the process of implementing community service activities, due to good cooperation from partners and a high intention to learn from the training participants.